2021
DOI: 10.1155/2021/5523145
|View full text |Cite
|
Sign up to set email alerts
|

Tomographic Evaluation of the Internal Adaptation for Recent Calcium Silicate-Based Pulp Capping Materials in Primary Teeth

Abstract: Objectives. To evaluate the internal adaptation of recent pulp capping materials (TheraCal and Biodentine) relative to MTA when used as indirect pulp capping for primary teeth. Materials and Methods. Thirty primary molars were randomly allocated into three groups, group (A) was TheraCal, group (B) was Biodentine, and MTA was the control group (C). A standardized round class-V cavity (1.5 mm diameter and 2 mm depth) was prepared using a milling machine on the buccal surface of each tooth with the pulpal floor l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 54 publications
1
9
0
Order By: Relevance
“…The clinical and radiographic results of TheraCal and Biodentine suggest their use as an alternative material for IPC in young permanent molars with greater success [13] . Finally, Biodentine and MTA showed a comparable result in terms of their internal adaptation on the dentin surface of primary teeth, and both were better than TheraCal [20] . This treatment has high success rates (over 90%), however, it will depend mainly on the size of the lesion being treated and its time of evolution, beyond the material of choice.…”
Section: Methodsmentioning
confidence: 84%
“…The clinical and radiographic results of TheraCal and Biodentine suggest their use as an alternative material for IPC in young permanent molars with greater success [13] . Finally, Biodentine and MTA showed a comparable result in terms of their internal adaptation on the dentin surface of primary teeth, and both were better than TheraCal [20] . This treatment has high success rates (over 90%), however, it will depend mainly on the size of the lesion being treated and its time of evolution, beyond the material of choice.…”
Section: Methodsmentioning
confidence: 84%
“…The heterogeneity observed in these outcomes may also be attributed to several bonding variables, including sample storage conditions, sample characteristics, surface preparation techniques, thermal cycling, and film thickness. Furthermore, variations in the results may arise owing to the diverse physical properties of calcium silicate-based biomaterials, variations in radioactive components, discrepancies in the production process, purity of the components, and differences in hydration products [ 6 , 25 ]. Although the primary constituent of the biomaterials utilized in our research is calcium silicate, the recently developed MMTA incorporates zirconium oxide instead of bismuth oxide, unlike WMTA.…”
Section: Discussionmentioning
confidence: 99%
“…Another plausible explanation might be the lower adaptation of TheraCal PT to dentin, impairing its sealing ability, especially with wider exposures in PP. One study revealed that the gap between TheraCal LC and dentin in primary teeth was significantly higher than that with MTA and Biodentine [46]. Thus, although this could be true for TheraCal PT, no studies have evaluated this parameter.…”
Section: Discussionmentioning
confidence: 99%